Effects of two-year oral health information provision on changes in gingival crevicular fluid in male day-night shift workers - Mio Naito; Kayoko Shinada; Naoko Seki; Masako Akiyama; Ryoko Yamamoto; Tomoko Onishi; Katsuko Taniyama; Ikuko Morio (Elsevier, 2022)
Background/purpose: Although dental diseases are related to systemic diseases and daily habits and are known to affect the quality of life, little attention has been paid to the importance of oral hygiene in Japanese working-age adults. We, thus, aimed to assess changes in the periodontal condition of working-age adults after providing regular oral health information at their workplace for two years. Materials and methods: Two years of oral health information were provided to workers at four printing companies. The effectiveness thereof was assessed using gingival crevicular fluid (GCF) test results-lactoferrin (Lf), alpha-1-antitrypsin (AT), and aspartate aminotransferase (AST). Questionnaires on health literacy (HL) and dental terminology were also administered to the workers during annual check-ups. Results: The baseline survey participants included were 234 male workers, of which 104 workers followed the same work schedule/day-night shifts and completed the two-year follow-up survey were examined. Providing continuous oral health information with regular updates did not improve participants' self-administered GCF tests (Lf: P = 0.272, AT: P = 0.723, and AST: P = 0.067), and there were no significant changes in HL, perceived symptoms, and use of interdental cleaning tools. Conclusion: Direct oral health education or examination might be necessary for working-age adults to achieve optimum oral conditions, and one-on-one health information provision might not improve their oral condition. A combination of methods to provide oral health promotion must be considered.